Thermostimulated luminescence of plasma electrolytic oxidation coatings on 6082 aluminium surface - Zolotarjovs, Aleksejs; Smits, Krisjanis; Laganovska, Katrina; Bite, Ivita; Grigorjeva, Larisa; Auzins, Krisjanis; Millers, Donats; Skuja, Linards (Elsevier Ltd, 2019)
For decades, plasma electrolytic oxidation (PEO) coatings are actively studied and applied to protect the surface of various valve metals from chemical or mechanical damage. However, over the last couple of years intense research is being done to explore additional possibilities of the PEO coatings apart from their classical application. One of the possible additional uses is thermostimulated luminescence dosimetry that is already widely applied for environmental and health monitoring. This research proposes a method to produce a novel functional coating on aluminium surface exhibiting intense thermostimulated luminescence signal that could be used for dosimetry of ionizing radiation. The result was achieved using plasma electrolytic oxidation with modified electrolyte to introduce carbon ions into the oxide thus inducing defects in the crystalline structure of the coating. Al6082 aluminium alloy was used as a substrate, KOH and ethanol mixture as an electrolyte. A bipolar pulsed regime was used for 15 min. The obtained coating combines the desired luminescence properties with a good mechanical stability due to the relatively hard cubic phase of the coating. Scalability of the technology and low production cost makes the coatings prospective for various practical applications.
Financial support provided by Scientiﬁc Research Project for Students and Young Researchers Nr. SJZ/2016/12 realized at the Institute of Solid State Physics, University of Latvia is greatly acknowledged. Authors are grateful to R. Ignatans for measurements and analysis of XRD spectra and ElGoo Tech ltd. for providing PEO equipment.
Keywords: Plasma electrolytic oxidation; PEO; Dosimetry; TSL; Alumina; Luminescent coating; Research Subject Categories::NATURAL SCIENCES:Physics